The Prospects of Succinates’ Use under Hypoxic Conditions in COVID-19 - Yu. Р. Orlov; V. V. Afanasyev; I. A. Khilenko (Антибиотики и Химиотерапия, 2021)
The aim of the work was the search for materials from experimental and clinical studies reflecting the pathogenetic role of the possible use of succinates for the correction of hypoxia in COVID-19. Materials and methods. 79 foreign and domestic literature sources were analyzed concerning the pathogenesis of COVID-19 and the pathogenetic role of succinates in hypoxia under conditions of COVID-19, oxidative stress, and diaphragmatic dysfunction were analyzed. The literature search was carried out using Pubmed and ELIBRARY.ru databases. Results. As the analysis of the literature has shown, tissue hypoxia is the basis of COVID-19 pathogenesis, triggering the entire cascade of  pathomorphological events leading to the development of multiple organ failure. A number of experimental and clinical studies (on a fairly large number of patients) reflect the positive effect of tissue hypoxia correction using succinates, both in adult patients and in children with a different spectrum of pathology associated with acute respiratory failure syndrome. Conclusion. Analysis of literature data allows to substantiate the prospect of using preparations containing succinate (reamberin, cytoflavin) in the complex therapy of severe cases of COVID-19.